Determinants of macroeconomics factors affecting Malaysia stock price volatility / Nik Muhammad Farid Afifuddin Nik Fakarudin - Nik Fakarudin, Nik Muhammad Farid Afifuddin (2022)
Every trader, whether a scalper, intraday trader, swing trader, or position trader, is sensitive to stock market volatility. This is because they are always looking to make a profit on each of their trades. As a result, they are always aware of any major news so that it does not interfere with their technical analysis. The researcher will conduct research on the relationship between macroeconomic factors and stock market volatility in this study. The purpose of this study is to investigate the factors that influence the volatility of the Malaysian stock market (FBMKLCI) by using the unemployment rate, currency exchange rate, interest rate, and inflation rate as macroeconomic variables. This study was conducted using the regression and correlation analysis to identify macroeconomic factors that influence the volatility of Malaysian stock prices (FBMKLCI) using E-views application version 12 based on annual data for variables from 2011 to 2020. The result that can be made from this study is that the inflation rate and interest rate have shown a significant relationship with the volatility of Malaysian stock prices. As for the unemployment rate and currency exchange rate, it shows the opposite, that is, they both have an insignificant relationship with the volatility of Malaysian stock prices.